Challenges of pain masking in the management of soft tissue disorders: optimizing patient outcomes with a multi-targeted approach. (May 2014) - Speed, Cathy; Wolfarth, Bernd
Abstract Current approaches to managing soft tissue injuries often rely upon the use of non-steroidal anti-inflammatory drugs (NSAIDs). The use of NSAIDs in this manner is contentious, and some believe that the risks of using NSAIDs can outweigh any potential benefit. In this article the issues of toxicity, pain masking and return to full activity are reviewed, and an alternative strategy for the management of inflammation in soft tissue injuries is proposed. We consider that a multi-targeted approach has the potential to improve healing, reduce additional injury from premature return to full activity as a consequence of pain masking, and improve prognosis for many patients with soft tissue injuries.